2006
DOI: 10.1007/s00417-006-0319-1
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunction of transmission in the inner retina: incidence and clinical causes of negative electroretinogram

Abstract: The incidence of a negative ERG can differ between the laboratories depending on the causes for ERG recording and was in our laboratory 2.9% in a consecutive series of patients with inherited or acquired retinal degenerations. A disorder characteristically associated with negative ERG (e.g. XRS, CSNB, MAR) was diagnosed in 53% of these patients, whereas in 47% the negative ERG indicated an unexpected post-receptoral dysfunction, e.g. in cone (-rod) dystrophy or RP. The ON-bipolar pathway was affected in most c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 19 publications
3
37
1
Order By: Relevance
“…However, two studies have assessed the frequency and various causes of negative ERGs: Koh et al [16] and Renner et al [17] reported negative ERG frequencies of 4.8 and 2.9%, respectively, at their centers. Although some of the disorders associated with negative ERGs would be expected to be more common in children, such as Juvenile Neuronal Ceroid Lipofuscinosis or Duchenne Muscular Dystrophy [18,19], many others seem more likely to be diagnosed in adults (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, two studies have assessed the frequency and various causes of negative ERGs: Koh et al [16] and Renner et al [17] reported negative ERG frequencies of 4.8 and 2.9%, respectively, at their centers. Although some of the disorders associated with negative ERGs would be expected to be more common in children, such as Juvenile Neuronal Ceroid Lipofuscinosis or Duchenne Muscular Dystrophy [18,19], many others seem more likely to be diagnosed in adults (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Koh et al [2] and Renner et al [30] have reviewed the causes of negative ERGs for patients seen in their clinics. Rod-cone or cone (-rod) dystrophies represented a large proportion of such cases in both clinics, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…1 [31], the fact that this patient has neither been diagnosed with cutaneous melanoma [32], nor has complained of a recent onset of night blindness [31,32] and/or photopsias [2,6] argues against a diagnosis of MAR. Although the patient did not report problems with his night vision, a diagnosis of CSNB should be considered, as it is a frequent cause of a bilateral negative ERG [2,30]. CSNB1 and CSNB2 can be distinguished primarily by differences in the isolated rod ERG response (not detectable in most CSNB1 patients; detectable but smaller than normal in most CSNB2 patients), and by the cone-mediated responses, which are relatively normal in CSNB1 but markedly abnormal in CSNB2 [3,33,34].…”
Section: Discussionmentioning
confidence: 99%
“…The absence of the b-wave in the ERG has been associated with the non-progressive disease congenital stationary night blindness (CSNB). It has been reported that between 2.9 and 4.8% of the human population has a negative ERG and the underlying cause of the vast majority of negative ERGs is CSNB (Koh et al, 2001;Renner et al, 2006;Kim et al, 2012).…”
Section: Electroretinogrammentioning
confidence: 99%